2019
DOI: 10.1159/000506511
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics Associated with the Likelihood to Use Paid Home Care for People with Dementia among South African Muslims

Abstract: Background: In societies where the value of filial piety is observed, a preference for caregiving to take place at home exists. In fact, institutional and paid home care for people with dementia (PWD) are still taboo in some Muslim societies. However, economic development and globalisation have resulted in intergenerational separation, thus impacting the ability by young adults to provide care for the elderly at home. Objective: We establish the demographic characteristics most likely to be associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…131 A study in South Africa showed that less than one third of respondents were willing to pay for formal home caregivers, with higher education, female sex, and older age associated with willingness to pay. 132 The challenges of formal care setting include the risk of delirium associated with dementia due to infective causes. 133,134…”
Section: Living With Dementia In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…131 A study in South Africa showed that less than one third of respondents were willing to pay for formal home caregivers, with higher education, female sex, and older age associated with willingness to pay. 132 The challenges of formal care setting include the risk of delirium associated with dementia due to infective causes. 133,134…”
Section: Living With Dementia In Africamentioning
confidence: 99%
“…Negative attitudes to formal care exist among some family members and in some societies irrespective of economic status, with religious beliefs contributing to the perspective 131 . A study in South Africa showed that less than one third of respondents were willing to pay for formal home caregivers, with higher education, female sex, and older age associated with willingness to pay 132 . The challenges of formal care setting include the risk of delirium associated with dementia due to infective causes 133,134 .…”
Section: Current Evidencementioning
confidence: 99%
“…Similarly, studies of South African Muslims (Ramaboa and Fredericks, 2019) and Muslim immigrants to France from North Africa (Duguet et al, 2016) examined the filial obligation of adult children to provide support for their aging parents. Both studies cast filial piety as an integral aspect of Islam and found that greater endorsement of this filial obligation corresponded to the increased behavior of caring for an aging parent in the home.…”
Section: Intergenerational Solidarity: Filial Expectations and Obligamentioning
confidence: 99%
“…In their study, Russell (2003) reported that 86 per cent of rural black South African participants, 60 per cent of urban black South African participants and 49 per cent of urban white South African participants disagreed with the idea of sending an older relative to an institution to be cared for. However, Ramaboa and Fredericks (2019) showed that among their Muslim sample, there was also support for paid care workers in the home, and in Hoffman's (2016) study, younger adults were more open to placement in aged-care homes as a way of balancing employment with care responsibilities. Research on care at home has mostly examined care for people living at home with dementia (Pretorius et al, 2009;Gurayah, 2015;Ramaboa and Fredericks, 2019;Smith et al, 2020;2022) and Alzheimer's disease (Hendricks-Lalla and Pretorius, 2020;Mahomed and Pretorius, 2021), and shows that family care is not only associated with increased support needs (Smith et al, 2020), but also linked to a negative impact on quality of life (Hendricks-Lalla and Pretorius, 2020) and family relations (Gurayah, 2015;Smith et al, 2020).…”
Section: Introductionmentioning
confidence: 90%
“…Decisions, and families' capacities, to care for an older person are shaped by many factors, including demographic change, migration and the impact of HIV in limiting the capacity of the middle generation to provide care to older persons (Schatz and Seeley, 2015;. The research that exists indicates variation in support for institutional eldercare (Russell, 2003;Ramaboa and Fredericks, 2019). In their study, Russell (2003) reported that 86 per cent of rural black South African participants, 60 per cent of urban black South African participants and 49 per cent of urban white South African participants disagreed with the idea of sending an older relative to an institution to be cared for.…”
Section: Introductionmentioning
confidence: 99%